2022
DOI: 10.3345/cep.2022.00122
|View full text |Cite
|
Sign up to set email alerts
|

Mediation effect of cord blood cortisol levels between maternal prepregnancy body mass index and birth weight: a hospital-based cross-sectional study

Abstract: Background: Changes in maternal weight affect the maternal and fetal hypothalamicpituitary-adrenal (HPA) axis, influencing birth weight and contributing to the fetal origin of adult diseases (Barker's hypothesis). This study primarily focused on cord blood cortisol levels and identified the association between maternal pre-pregnancy body mass index (pre-BMI) and birth weight. It also assessed cord blood lipid profile changes related to maternal pre-BMI, birth weight, and cord blood cortisol levels.Purpose: To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Studies have also shown that excessive fetal exposure to GCs is associated with the downregulation of fetal glucocorticoid receptor (GR) and mineralocorticoid receptor (MR) and impairment of the feedback regulation of the HPA axis in both infancy and adulthood [5,13,40,41]. Cross-sectional research has indicated a connection between low birth weight and disrupted functioning of the HPA axis, leading to elevated levels of GC in adulthood [10,[42][43][44]. In addition, the association between low birth weight and the development of T2DM was first reported in studies by Hales et al, who demonstrated a several-fold increase in the incidence of glucose intolerance and T2DM in adult men who were born with low birth weight compared with those born with normal birth weight [39,45].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that excessive fetal exposure to GCs is associated with the downregulation of fetal glucocorticoid receptor (GR) and mineralocorticoid receptor (MR) and impairment of the feedback regulation of the HPA axis in both infancy and adulthood [5,13,40,41]. Cross-sectional research has indicated a connection between low birth weight and disrupted functioning of the HPA axis, leading to elevated levels of GC in adulthood [10,[42][43][44]. In addition, the association between low birth weight and the development of T2DM was first reported in studies by Hales et al, who demonstrated a several-fold increase in the incidence of glucose intolerance and T2DM in adult men who were born with low birth weight compared with those born with normal birth weight [39,45].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the possibility has been raised that maternal or fetal blood cortisol levels may mediate the relationship between maternal pre-BMI or GWG and birth weight. Therefore, Selvam et al [ 7 ] conducted a hospital-based cross-sectional study to investigate whether cord blood cortisol mediates pre-BMI or GWG and birth weight after assuming cortisol as a hormone representing the HPA axis. The authors reported that the mediation effect of cord blood cortisol on maternal pre-BMI or GWG and birth weight was not statistically significant [ 7 ].…”
mentioning
confidence: 99%
“…Therefore, Selvam et al [ 7 ] conducted a hospital-based cross-sectional study to investigate whether cord blood cortisol mediates pre-BMI or GWG and birth weight after assuming cortisol as a hormone representing the HPA axis. The authors reported that the mediation effect of cord blood cortisol on maternal pre-BMI or GWG and birth weight was not statistically significant [ 7 ]. Jin et al [ 8 ] analyzed all steroid hormones in the maternal-placental-fetal unit and found that corticosterone had a partial mediating effect of 3.48% and cortisol and corticosterone had a mediating effect of 4.33% and 5.38%, respectively, when the GWG was higher than the Institute of Medicine’s recommendation.…”
mentioning
confidence: 99%
See 2 more Smart Citations